The Pursuit Of Happiness In American Mind And In Javanese Thought - Djuhertati Imam Muhni (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2002)
society has a concept of happiness and has a way to pursue it. This essay tries to bring out some of these concepts and its pursuits as seen in two different societies, namely American and Javanese. The discussion is more of a vision on the theme rather than a comparative study. The essay falls into two sections: the first describes some important facts about American pursuits of happiness and the second discusses the pursuit of happiness in one small part of the Javanese thoughts or Kejawen, namely Soerjomentaram’s philosophy of Ngelmu Beja.